2018
DOI: 10.1016/bs.aesp.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Processes in Social Perception

Abstract: In this chapter, we describe how a simple attentional mechanism can account for a wide variety of phenomena in social perception. According to Attention Theory (Kruschke, 1996, 2003), people preferentially attend to differentiating information in order to maximize category learning. When learning multiple social categories, people attend to all features that characterize the first-learned category but shift their attention to features that uniquely distinguish a later-learned category from the first. As a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…However, a critical difference between these studies and the present approach was that the positive evaluative information was redundant. That is, the second tribe or the second brand showed similar positive information and the primacy effect was predictable from attention theory, whereby novel information has an advantage over redundant information (Sherman et al., 2009; Huang & Sherman, 2018). Here, in both experiments, the second group showed distinct evaluative information, either on another dimension of social perception (i.e., communion vs. agency), or on the relevance for the job dimension (i.e., relevant vs. irrelevant).…”
Section: Discussionmentioning
confidence: 91%
“…However, a critical difference between these studies and the present approach was that the positive evaluative information was redundant. That is, the second tribe or the second brand showed similar positive information and the primacy effect was predictable from attention theory, whereby novel information has an advantage over redundant information (Sherman et al., 2009; Huang & Sherman, 2018). Here, in both experiments, the second group showed distinct evaluative information, either on another dimension of social perception (i.e., communion vs. agency), or on the relevance for the job dimension (i.e., relevant vs. irrelevant).…”
Section: Discussionmentioning
confidence: 91%
“…One reason that people pursue this strategy is because stereotypeinconsistent information is viewed as inconsequential and "uninformative about the true nature of the target" (Bastian and Haslam, 2007). This is in particular true for minority groups; when thinking about members of minority groups, people tend to focus on stereotypical traits that distinguish these members from members of the majority group (Huang and Sherman, 2018).…”
Section: Gender Biased Information Acquisitionmentioning
confidence: 99%
“…Individuals are prone to remember the stereotypic information more robustly (Berthold, Steffens, & Mummendey, 2019;Huang & Sherman, 2018). For instance, a new manuscript in a Turkish sample showed that traits such as "talkative" were more robustly bound with women actors, and inferences were made in a gender stereotypic way by more sexist participants (Soylu, 2017).…”
Section: Classification Model For the Intervention Studiesmentioning
confidence: 99%